THE IDEAL RENAISSANCE COURTIER IN SIR PHILIP SIDNEY’S ASTROPHIL AND STELLA AND THE NOBLE LOVER IN UZBEK CLASSICAL POETRY - Ajikulova Ayajan Rinatovna, Khamitov Eldorbek Erkinovich (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
ABSTRACT: This paper explores the shared moral and intellectual ideals of love as portrayed in Sir Philip Sidney’s Astrophil and Stella and in the works of Uzbek classical poets such as Alisher Navoi and Zahiriddin Muhammad Bobur. Despite belonging to different cultural and religious traditions, both literary movements celebrate love as a means of self-cultivation and moral perfection. Sidney’s Astrophil reflects the Renaissance ideal of the refined and self-disciplined courtier, whose emotional struggle becomes a path toward intellectual and ethical harmony. In contrast, Navoi’s and Bobur’s noble lovers embody the Sufi-inspired pursuit of divine beauty through sincerity, loyalty, and inner discipline. The study highlights how both traditions, grounded in Christian humanism and Islamic mysticism, converge in their elevation of the individual’s moral and spiritual growth through love.